1986
DOI: 10.2118/13215-pa
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Crude-Oil-Induced Wettability Changes on Oil Recovery

Abstract: Morrow, Norman R., SPE, New Mexico Petroleum Recovery Research Center Petroleum Recovery Research Center Lim, Hau T., SPE, New Mexico Petroleum Recovery Research Center Ward, Jill S., SPE, New Mexico Petroleum Recovery Research Center Summary Displacements in strongly water-wet cores; are compared with results of similar tests for a mixed wettability condition induced by a selected crude oil. Cores exposed to crude oil showed weakly water-wet imbibition behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
141
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(147 citation statements)
references
References 18 publications
4
141
0
Order By: Relevance
“…Since asphaltene adsorption is virtually irreversible (Morrow et al, 1986;Hirasaki et al, 1990;Dubey and Waxman, 1991), we postulate that ali thicknesses of oil films deposited on asphaltene-coated surfaces are stable, lt follows that the oil-film disjoining pressure is purely repulsive. Thus, the solid surface is completely wetted by oil, and the newly created meniscus establishes a contact angle of 180°measured through the water phase.…”
Section: Water-wet Porementioning
confidence: 99%
See 2 more Smart Citations
“…Since asphaltene adsorption is virtually irreversible (Morrow et al, 1986;Hirasaki et al, 1990;Dubey and Waxman, 1991), we postulate that ali thicknesses of oil films deposited on asphaltene-coated surfaces are stable, lt follows that the oil-film disjoining pressure is purely repulsive. Thus, the solid surface is completely wetted by oil, and the newly created meniscus establishes a contact angle of 180°measured through the water phase.…”
Section: Water-wet Porementioning
confidence: 99%
“…Oil-drop adhesion tests provide a simple approach to characterize the wetting behavior of crude oils against solid surfaces (Morrow et al, 1986;Buckley et al, 1989;Buckley and Morrow, 1990). When adhesion occurs, it is found that the solid/oil/water boundary is fixed or "pinned" at the three-phase contact line (Morrow, 1990).…”
Section: Thin Films and Wettabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Oil recovery mechanisms strongly depend on the wettability of the reservoir rock [1,21,23]. Many natural rocks are water-wet.…”
Section: Introductionmentioning
confidence: 99%
“…Although the translucent epoxy model, which has a strong hydrophobic surface, has been utilized for the study of water flow through rock fractures [Su, 1995;Yeo et al, 1998;Brown et al, 1998], few investigations have been conducted on the effects of a change in the surface wettability on the flow of ground water through a fracture. The importance of surface wettability has been recognized in the area of petroleum engineering, but studies have focused on the enhancement of oil recovery, not the water flow through a hydrophobic surface [Morrow et al, 1986;Jadhunandan and Morrow, 1995].…”
Section: Introductionmentioning
confidence: 99%